If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4x = 2 + 8x Solving 5 + 4x = 2 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 5 + 4x + -8x = 2 + 8x + -8x Combine like terms: 4x + -8x = -4x 5 + -4x = 2 + 8x + -8x Combine like terms: 8x + -8x = 0 5 + -4x = 2 + 0 5 + -4x = 2 Add '-5' to each side of the equation. 5 + -5 + -4x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 2 + -5 -4x = 2 + -5 Combine like terms: 2 + -5 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75
| 1/(2x-4)=31/24 | | -5.4-7.8x=-78.4 | | ln(x)=ln(2) | | 2/3x-9=1/2x-8 | | 10t-4=-3 | | 31=7k-4 | | -4(2x+3)=2(3x-2) | | 2.5x+46.8=14.7-8.2x | | 2(4w+1)-2w=5w-1 | | 100/×=-4 | | -10x=8x-7 | | 3x-59=34 | | 1/2x-400=5000 | | 2/7=35/h | | X+9-4x=-3x-3 | | g=2(2)+1 | | 4x+7-2x=-4 | | x+0.2x=53 | | 1/2-400x=5000 | | 4/5x=-141/35 | | g=2(0)+1 | | 10x-131=5x-6 | | 12/y=30/9 | | g=2(-1)+1 | | 7x+6=66 | | 6x-7+2x+8=x+5-2x+12 | | g=2(-2)+1 | | -3x+4=5x-8 | | (6x-1)/2=9 | | (x+12)(x-1)=2(x-6)-20 | | 6x+3*(-3)=9 | | 6x-1/2=9 |